The Impact of Globalization on Gender Roles and Cultural Practices Among Women in Tamil Nadu - Muthu, Saraswathi Priya; Kočí, Kateřina; Grančayová, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This master’s thesis study how globalization has reshaped cultural practice and gender roles among women across three generations in urban and rural Tamil Nadu. Tamil Nadu’s prompt educational expansion, industrial growth and urbanization between determined traditional norms. The main research question is “How have women across three generations in urban and rural Tamil Nadu negotiated the tensions between traditional cultural expectations and the opportunities and pressure created by globalization?’’. The thesis guided by postcolonial feminism and intersectionality, the study examines three dimensions which are economic participation, education/empowerment and cultural identity which highlighting how caste, class, colonial legacies and location mediate globalization’s uneven effects. A mixed-methods case study design integrates qualitative semi-structured interviews (primary data) with secondary quantitative data from the National Family Health Survey, Census of India and Tamil Nadu government reports, alongside secondary qualitative sources including peer reviewed monographs and journal articles on Tamil Nadu women’s empowerment. The thematic analysis (Braun & Clarke,2006) spot patterns like rising urban female labour force participation and delayed marriage, in contrasted with rural limitations. A finding reveals women’s organizations in hybridizing traditions older generations maintained domestic roles between limited mobility, mid generations accessed informal work and education via Dravidian reforms and younger generation rural youth faced determined patriarchal barriers, while urban women adopt salaried jobs, digital self-expression and delayed marriage. Such pattern shows globalization’s dual role-expanding choices while strengthening inequalities filtered through local postcolonial contexts.
Empirically, a mixed -methods triangulation provide refinement insights into Tamil Nadu’s transformations, contributing to Global South gender studies. Policy implications urge culturally sensitive reforms to foster equitable empowerment.
Vedoucí práce: Kateřina Kočí
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses